PPS thin film copper-plated current collector for battery negative electrode and preparation process of PPS thin film copper-plated current collector

By introducing carboxyl functional groups into the PPS base film and combining corona activation and magnetron sputtering technology, a strong bonding layer is formed, which solves the problems of insufficient heat resistance and poor bonding ability of the base film, and significantly improves the performance and stability of the battery. sex.

CN119361714APending Publication Date: 2025-01-24SICHUAN ZHONGKE XINGYE HIGH-TECH MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411260085.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The base film of the existing composite fluid collector is insufficient heat resistance, which leads to accumulated heat during the composite fluid processing, resulting in heat deformation, holes and fracture of the base film. At the same time, the bonding ability of the base film and the copper layer is poor, affecting the battery. performance.

Method used

A PPS-based film is used that introduces carboxyl functional groups when the molecular chain is terminated, and a conductive seed copper layer is deposited through corona activation treatment and vacuum magnetron sputtering to form a double-layer copper plating layer. The bonding layer undergoes a cross-linking reaction in an acidic environment. Form a three-dimensional network structure to enhance the bonding force between the base film and the copper layer.

Benefits of technology

Improve the heat resistance and mechanical performance of the PPS base film, enhance the binding force between the base membrane and the copper plating layer, reduce the requirements for the equipment when plating, improve the cycle use performance of the battery, and reduce the compound set. The risk of fluid in the electrolyte is dissolved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361714A_ABST
    Figure CN119361714A_ABST
Patent Text Reader

Abstract

The invention discloses a PPS film copper-plated current collector for a battery negative electrode and a preparation technology, and belongs to the technical field of battery manufacturing and film manufacturing, the PPS film copper-plated current collector for the battery negative electrode comprises a base film, the horizontal surface of the PPS base film is coated with a copper-plated layer, a bonding layer is formed at the contact position of the PPS base film and the copper-plated layer, and the bonding layer is coated with a copper-plated layer. The PPS base film is formed by mixing polyphenylene sulfide resin, a heat dissipation aid and microporous particles, an activation layer is formed on the horizontal surface of the PPS base film through corona, a copper target is deposited on the activation layer through sputtering to form a conductive seed copper layer, and the conductive seed copper layer is thickened through a water electroplating process to form a copper plating layer. The polyphenylene sulfide resin subjected to end capping treatment is used as a base film, so that the defects of heat resistance and mechanical property of a PP film or a PET film as the base film are overcome, the retention time of the base film in magnetron sputtering and evaporation equipment is prolonged, the number of times of physical vapor deposition copper plating is reduced, the mechanical property is optimized, and the limitation of the traction speed in the equipment is reduced; and the production rate of the copper-plated current collector is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery manufacturing and thin film manufacturing, and specifically relates to a PPS thin film copper-plated current collector for a battery negative electrode and a preparation process thereof. Background Art

[0002] As a device that converts chemical energy into electrical energy, the core components of a battery include the positive electrode, negative electrode and electrolyte. Among these components, copper foil is widely used in the negative electrode of the battery due to its excellent conductivity and chemical stability. In particular, composite copper foil, also known as composite current collector, combines electrolytic copper foil with organic film through a specific preparation process, thereby expanding its application range.

[0003] The preparation process of electrolytic copper foil usually involves the following steps: Raw material preparation: First, it is necessary to prepare the raw materials of electrolytic copper foil, including high-purity copper raw materials and solutions for electrolysis. Electrolytic deposition: The copper raw materials are placed in the electrolytic cell. Through the electrolysis process, the copper ions are reduced to pure copper on the cathode (usually copper foil), thereby forming electrolytic copper foil. Post-processing: After the electrolytic copper foil is completed, a series of post-processing steps are required, such as cleaning and annealing, to improve the performance of the copper foil. Composite process: In order to expand the application range of copper foil, a composite process can be used to combine electrolytic copper foil with organic film. This usually involves bonding and laminating the copper foil with the organic film to form a composite copper foil.

[0004] The advantages of composite current collectors include: Improved performance: Composite copper foil can combine the conductive properties of copper foil and the specific properties of organic films to improve overall performance. Expanded application scope: By compounding different types of organic films, the application scope of copper foil can be expanded to make it suitable for different fields and application scenarios. Enhanced stability: Organic films can enhance the chemical stability of copper foil, so that it can maintain good performance even in harsh environments. Reduced cost: The production cost of composite copper foil is usually lower than that of a single material, thereby reducing overall costs. In short, through the preparation process and composite process of electrolytic copper foil, composite copper foil with excellent performance can be prepared, thereby expanding its application range and meeting the needs of different fields.

[0005] The organic films commonly used in existing composite current collectors are mostly PET films or PP films. The base film has insufficient heat resistance, and heat will accumulate during the processing of the composite current collector, which will cause the base film to deform due to heat and may further cause holes and base film breakage. The existing PET / PP base film has poor bonding ability with the copper layer, and the copper layer may peel off and swell in the electrolyte, limiting the battery performance. In view of this, the present invention provides a PPS thin film copper-plated current collector for battery negative electrode and a preparation process. Summary of the invention

[0006] The present invention aims to solve one of the following technical problems to a certain extent. In view of the problem of insufficient heat resistance of the above-mentioned base film, the present invention proposes a preparation process of a PPS base film, which improves the mechanical properties of the base film while solving the heat resistance problem. At the same time, a capping agent is added to the post-synthesis stage of the high molecular weight resin to improve the bonding force between the base film and the copper layer. In the process of preparing the composite current collector, the method of obtaining the conductive copper layer is optimized to achieve the effect of improving the stability of the base film structure and preventing the copper layer from falling off. Specifically, a PPS thin film copper-plated current collector for battery negative electrode and a preparation process are provided.

[0007] The technical solution adopted to solve the above technical problems is:

[0008] A PPS film copper-plated current collector for battery negative electrode comprises a base film, wherein the base film is a PPS base film into which carboxyl functional groups are introduced when the molecular chains are terminated, a copper-plated layer is coated on the horizontal surface of the PPS base film, and a bonding layer is formed at the contact position between the PPS base film and the copper-plated layer.

[0009] There are two copper-plated layers, which are arranged on the top and bottom surfaces of the PPS base film respectively. In an acidic environment, the carboxyl functional groups of the PPS base film and the copper ions on the contact surface of the copper-plated layer react chemically to form copper carboxylates, thereby achieving a cross-linking reaction to form a three-dimensional network structure bonding layer.

[0010] Furthermore, the PPS base film is made of polyphenylene sulfide resin, heat dissipation aid and microporous particle melt-casting film, and the thickness of the PPS base film is 3 μm.

[0011] Through the above technical solution, the raw materials are mixed and solidified into a thin film PPS base membrane through drawing. The nano-scale microporous particles can ensure the mechanical properties of the PPS base membrane, which does not need to be too thick, saves materials and can optimize the thickness of the assembled battery, contributing to the lightweighting of the battery.

[0012] Furthermore, an activation layer is formed on the horizontal surface of the PPS base film by corona, a copper target is deposited on the activation layer by sputtering to form a conductive seed copper layer, and the conductive seed copper layer is thickened by a water electroplating process to form a copper-plated layer. The total thickness of the PPS base film, the two copper-plated layers and the two bonding layers is 6.5 μm.

[0013] Through the above technical solution, the contact position between the PPS base film and the copper-plated layer is heated, which can effectively remove the volatile additives on the surface of the composite current collector, thereby reducing the pores in the copper-plated layer 2. The heating causes the base film and the copper layer to undergo a certain degree of thermal shrinkage, which can increase the mechanical bite between the two, and then form a bonding layer by physical means.

[0014] A preparation process of a PPS film copper-plated current collector for a battery negative electrode comprises the following steps:

[0015] S1, preparing a high molecular weight polyphenylene sulfide resin, adding a capping agent to cap the polyphenylene sulfide resin, and introducing a carboxyl functional group into the PPS molecular chain;

[0016] S2, the particles are melted, a heat dissipation aid and microporous particles are added, and the particles are cooled and solidified for granulation;

[0017] S3, cast film making process;

[0018] S4, biaxial stretching to form a PPS base film;

[0019] S5. The surface of the PPS base film is treated with corona activation to activate and enhance the bonding strength between the functional groups and the metal;

[0020] S6, depositing a conductive seed copper layer on the surface of the PPS base film by vacuum magnetron sputtering;

[0021] S7, water electroplating thickens the conductive copper plating layer to form a copper plating layer;

[0022] S8, heating, drying and purifying the composite current collector to promote cross-linking and curing between the PPS base film and the copper plating layer to form a bonding layer.

[0023] Through the above technical scheme, the optimization starts from the preparation of PPS resin, and the high molecular weight PPS resin is used for end-capping. While retaining good heat resistance and mechanical properties, the carboxyl functional group is introduced into the PPS molecular chain, which strengthens the bonding force between the PPS base film and the copper plating layer, and reduces the requirements for sputtering and evaporation equipment during copper plating. At the same time, the method of obtaining the conductive copper layer is optimized. A cloud treatment is used as a surface activation method for the PPS base film to improve the adhesion between the PPS base film and the subsequent copper plating layer, and provide good surface conditions for the deposition of the conductive seed layer. Subsequent surface treatment and heat treatment steps are added, and oxygen-containing functional groups and copper participate in the cross-linking reaction to form a three-dimensional network structure, which is transformed from simple physical adsorption or weak chemical bonds to compounds with higher bonding strength, thereby improving the bonding strength between the PPS base film and the copper plating layer, so that the conductive copper layer can be well preserved in the battery electrolyte and the battery cycle capacity is enhanced. At the same time, the excellent chemical resistance of the PPS base film itself can reduce the possibility of dissolution and failure of the composite current collector in the electrolyte.

[0024] Furthermore, the end-capping agent is carboxylic anhydride, specifically terephthalic anhydride.

[0025] Through the above technical scheme, terephthalic anhydride is added as a capping agent during the polymerization stage of the PPS resin to cap the resin. The capping agent reacts chemically with the PPS end group to form a stable end group structure, thereby retaining heat resistance and mechanical properties while enhancing the bonding force between the PPS base film and the copper layer.

[0026] Furthermore, the heat dissipation aid uses at least one of polybismaleimide resin, silicon nitride fiber, nano-silicon dioxide powder, and nano-fluorite powder, and the microporous particles use at least one of nano-TiO2, nano-Al2O3, and nano-SiO2.

[0027] Through the above technical scheme, the heat dissipation additives and microporous particles can effectively improve its heat resistance. The dispersion of these nano-scale microporous particles in the matrix can increase the rigidity of the polymer chain, promote polymer crystallization and increase the cross-linking degree of the polymer. They can play a reinforcing and filling role in the weaker micro-areas of the resin, thereby effectively improving the comprehensive performance of the composite material.

[0028] Furthermore, a corona treatment machine is used to perform double-sided corona treatment on the PPS base film. The corona treatment machine includes a high voltage power supply, at least two discharge electrodes and a rotating drum.

[0029] Through the above technical solution, after the PPS base film is corona treated, the PPS base film undergoes physical changes and its surface becomes rougher, thereby improving the adhesion between the PPS base film and the subsequent copper plating layer and providing good surface conditions for the deposition of the conductive seed layer.

[0030] Furthermore, the corona treatment machine can oxidize the carboxyl functional groups at the ends of the PPS molecular chains to generate one or more of keto functional groups, aldehyde functional groups or carbonyl functional groups.

[0031] Through the above technical scheme, oxygen-containing functional groups such as keto functional groups (-C=O), aldehyde functional groups (-CHO) or carbonyl functional groups (-CO-) can form coordination bonds and covalent bonds with copper, transforming from simple physical adsorption or weak chemical bonds to stronger chemical bonds. Oxygen-containing functional groups and copper participate in cross-linking reactions to form a three-dimensional network structure, thereby improving the bonding strength between the PPS base film and the copper-plated layer.

[0032] Furthermore, heating can oxidize the carboxyl functional groups at the ends of the PPS molecular chains into carbonyl functional groups, and coordination compounds are formed between the carbonyl functional groups and the copper ions on the surface of the copper plating layer.

[0033] Through the above technical scheme, the carboxyl functional group can react with the copper ions on the surface of the copper layer to form a cross-linked bond. At this time, the copper atom can provide an empty orbital, while the oxygen atom in the carbonyl group provides a lone pair of electrons, thereby forming a coordination compound, thereby tightly connecting the PPS base film and the copper-plated layer.

[0034] Furthermore, the volatile additives are removed by heating, and the contact surface between the PPS base film and the copper plating layer is thermally shrunk by the heating.

[0035] Through the above technical solution, the volatile additives evaporate, reducing the pores in the copper-plated layer, increasing the contact area and mechanical bonding force between the PPS base film and the copper-plated layer, thereby improving the bonding strength. Heating and drying helps to improve the interface contact between the PPS base film and the copper-plated layer, making the material surfaces fit more closely together.

[0036] The beneficial effects of the present invention are as follows:

[0037] (1) The present invention optimizes the base film material and uses the end-capped polyphenylene sulfide resin as the base film, thereby making up for the deficiencies in heat resistance and mechanical properties of PP film or PET film as the base film, increasing the residence time of the base film in the magnetron sputtering and evaporation equipment, reducing the number of physical vapor deposition copper plating, and optimizing the mechanical properties to reduce the limitation of the traction speed in the equipment, thereby effectively improving the production rate of the copper-plated current collector;

[0038] (2) The present invention optimizes the preparation and activation process of PPS resin, adds a capping agent to the material, caps the material with a high molecular weight PPS resin, introduces a carboxyl group at the end of the PPS resin molecular chain while retaining good heat resistance and mechanical properties, and cooperates with corona activation treatment to increase the bonding force between the base film and the copper layer, thereby reducing the requirements for sputtering and evaporation equipment during copper plating, and ensuring the battery recycling performance;

[0039] (3) The present invention optimizes the subsequent heat treatment process of the conductive copper layer and utilizes heating and drying treatment to increase the contact area and mechanical bonding force between the copper-plated layer and the base film. Heating causes the base film to form a coordination bond with the copper surface, and strengthens the bonding strength between the base film and the copper layer through physical and chemical mechanisms, so that the conductive copper layer can be well preserved in the battery electrolyte. At the same time, the excellent chemical resistance of the PPS base film can reduce the possibility of dissolution and failure of the composite current collector in the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a schematic structural diagram of the copper-plated current collector of the present invention;

[0041] Figure 2 It is a schematic diagram of the process of the present invention.

[0042] Reference numerals: 1, PPS base film; 2, copper plating layer; 3, bonding layer. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0044] like Figure 1As shown, this embodiment provides a PPS thin film copper-plated current collector for a negative electrode of a battery, comprising a PPS base film 1, the PPS base film 1 is made of polyphenylene sulfide resin as a substrate, and is prepared by melt granulation, cast film making, biaxial stretching and other steps. PPS has high thermal stability, high mechanical strength and rigidity, good chemical stability, and strong insulation ability. Therefore, the substrate performance as a copper-plated current collector is very excellent. The horizontal surface of the PPS base film 1 is coated with a copper-plated layer 2, and the copper-plated layer 2 has two layers. The copper-plated layer 2 is formed step by step on the top and bottom surfaces of the PPS base film 1 by vacuum magnetron sputtering deposition and water electroplating thickening to form a double-sided conductive copper-plated current collector;

[0045] The actual problem that this scheme seeks to solve is the peeling caused by insufficient heat resistance of the PPS base film 1 and poor bonding ability of the copper-plated layer 2. A specific configuration is provided below. When the PPS base film 1 itself is prepared, a carboxyl functional group is introduced when the molecular chain is capped. The capping can optimize the heat resistance of the PPS base film 1. A bonding layer 3 is formed at the contact position between the PPS base film 1 and the copper-plated layer 2. The bonding layer 3 is formed in an acidic environment by the reaction of the carboxyl functional group of the PPS base film 1 and the copper ions on the contact surface of the copper-plated layer 2 to form copper carboxylates, thereby realizing a cross-linking reaction to form a bonding layer 3 with a three-dimensional network structure.

[0046] In a further embodiment, the PPS base film 1 is formed by mixing polyphenylene sulfide resin, heat dissipation aid and microporous particles. After mixing, it is cured by drawing to form a film. The heat dissipation aid can further improve the heat resistance of the PPS base film 1. The thickness of the PPS base film 1 is 3μm. The nano-scale microporous particles, due to their large phase interface area, can play a reinforcing and filling role in the weaker micro-areas of the resin, thereby ensuring the tensile mechanical properties of the PPS base film 1. It does not need to be too thick to meet the use requirements, saving materials and optimizing the thickness of the combined battery, thereby contributing to the lightweight battery.

[0047] In a further embodiment, an activation layer is formed on the horizontal surface of the PPS base film 1 by corona, a copper target is deposited on the activation layer by sputtering to form a conductive seed copper layer, the conductive seed copper layer is thickened by a water electroplating process to form a copper-plated layer 2, and the contact position between the PPS base film 1 and the copper-plated layer 2 is heated to produce mechanical bite to form a bonding layer 3. The total thickness of the PPS base film 1, the two copper-plated layers 2 and the two bonding layers 3 is 6.5 μm, which meets the preparation requirements and can be used for the negative electrode production needs of micro batteries.

[0048] like Figure 1 and Figure 2 As shown, this embodiment provides a preparation process of a PPS thin film copper-plated current collector for a battery negative electrode, which is used to prepare a PPS thin film copper-plated current collector for a battery negative electrode, comprising the following steps:

[0049] (1) Optimization of the synthesis formula and process for preparing high molecular weight polyphenylene sulfide resin:

[0050] First, in terms of raw material selection, we use high-quality phenol and sodium sulfide as the main raw materials. In order to increase the molecular weight of polyphenylene sulfide resin, we use a multiphase catalytic system to improve the activity and selectivity of the polymerization reaction by screening and optimizing the catalyst. In the polymerization stage, we add a capping agent to cap the polyphenylene sulfide resin.

[0051] The polymerization reaction is generally completed within 4-6 hours, and the end-capping process takes 1-2 hours. During the processing, the polymerization kettle and the end-capping kettle can achieve reactions under high temperature and high pressure conditions to ensure the smooth progress of the polymerization reaction and the end-capping process. The agitator ensures that the raw materials are fully mixed to improve the reaction efficiency. The cooler is used to control the reaction temperature to prevent overheating. The temperature, pressure, stirring speed and other parameters are strictly controlled to ensure the smooth progress of the polymerization reaction.

[0052] It should be noted that the end-capping process involves an acid-base neutralization reaction to form a stable end group structure. By synthesizing carboxyl-terminated PPS, its thermal properties can be significantly improved. The synthesis of this modified PPS involves introducing a carboxyl functional group into the PPS molecular chain. After the introduction of the carboxyl group, the carboxyl group at the end of the PPS can react chemically with the copper surface to subsequently form a stable Cu-COOH coordination bond. The presence of the carboxyl group can also increase the polarity of the surface of the PPS base film 1, thereby enhancing the interaction with the copper-plated layer 2, so as to enhance the bonding force between the PPS base film 1 and the copper-plated layer 2.

[0053] (2) Granule Melting Granulation Process:

[0054] The end-capped polyphenylene sulfide resin particles are added to the extruder for melt granulation. The extruder adopts a twin-screw structure and has efficient and stable conveying and mixing performance;

[0055] The melt granulation process takes about 2-3 hours, which is adjusted according to the output and equipment model. The high temperature and high pressure of the extruder melt the polyphenylene sulfide resin particles and mix them evenly under the shearing action of the screw. Subsequently, the melt is extruded through the template to form uniform particles.

[0056] During this process, the molecular structure of polyphenylene sulfide resin does not change, and melting and granulation are achieved only through physical action. The twin-screw extruder has efficient and stable conveying and mixing performance to ensure the quality of the melt. The addition of heat dissipation additives and microporous particles improves the heat resistance of the resin. The cooling device allows the melt to solidify quickly, facilitating subsequent processing.

[0057] In a further embodiment, by uniformly mixing specific chemical additives into the resin, for example, using polybismaleimide resin, silicon nitride fiber, nano-scale silica powder, nano-scale fluorite powder, etc. as components of the functional masterbatch, these materials can improve the heat resistance of the resin and maintain its stable performance;

[0058] Adding nano fillers, such as nano TiO2, nano Al2O3 and nano SiO2, to the resin can effectively improve its heat resistance. The dispersion of these nano particles in the matrix can increase the rigidity of the polymer chain, promote polymer crystallization and increase the cross-linking degree of the polymer. Due to their large interfacial area, nano particles can play a reinforcing and filling role in the weak micro-area of ​​the resin, increase the interfacial force, and reduce the free volume, thereby effectively improving the comprehensive performance of the composite material.

[0059] By adding specific chemical additives or fillers, the chemical structure or physical structure of the resin is changed, thereby improving its heat resistance and thermal conductivity. At the same time, the rigidity of the polymer chain of the material can be optimized and the cross-linking degree of the polymer can be increased, thereby further improving the mechanical properties of the PPS base film 1 while solving the heat resistance problem.

[0060] (3) Casting film process:

[0061] The granulated material is added to the extruder for melt plasticization, and then cast film is formed through a casting die. The melt plasticization process takes about 1-2 hours, and the casting film forming process takes about 2-3 hours. Under high temperature and high pressure conditions, the material is melt plasticized and formed into a film through the casting die. The extruder and the casting die realize the melt plasticization and film forming of the material, and the cooling roller makes the film solidify quickly for easy winding.

[0062] (4) Biaxial stretching process:

[0063] The film obtained by casting is biaxially stretched under heating to adjust the thickness of the base film; the biaxial stretching process takes about 2-3 hours, which is adjusted according to the film thickness and equipment model. Through the stretching effect, the film is uniformly deformed in the longitudinal and transverse directions to achieve the required thickness;

[0064] The stretching machine realizes biaxial stretching of the film, the heating device ensures the temperature stability of the PPS base film 1 during the stretching process, and the cooling device makes the stretched PPS base film 1 solidify quickly to improve its performance. After biaxial stretching, the thickness of the PPS base film 1 reaches an appropriate range, laying the foundation for subsequent applications.

[0065] (5) Surface activation treatment of basement membrane:

[0066] Corona treatment is a physical modification method. It generates a high-intensity electric field on the surface of the base film to ionize the gas molecules in the air and generate plasma. The active particles in the plasma will collide with the surface of the PPS base film 1, thereby increasing its surface energy and improving its adhesion. The polarity of the surface of the PPS base film 1 is increased, which is beneficial to the subsequent bonding of the copper plating layer 2. The corona device treatment usually takes several minutes to more than ten minutes. The specific time depends on the material, thickness and required surface activity of the PPS base film 1.

[0067] A corona treater is used, which usually consists of a high voltage power supply, a discharge electrode and a rotating drum;

[0068] Specifically, after the corona treatment, the PPS base film 1 undergoes physical changes, the surface becomes rougher, the polarity is enhanced, the adhesion between the PPS base film 1 and the subsequent copper plating layer 2 is improved, and a good surface condition is provided for the deposition of the conductive seed layer;

[0069] It should be emphasized that corona treatment will cause chemical changes in the base film, affecting the bonding between the PPS base film 1 and the copper plating layer 2. The specific effects are as follows:

[0070] Improvement of surface energy: Corona treatment can increase the surface energy of the material and improve its wettability, which helps copper atoms to better contact with the corona-treated carboxyl-containing surface, thereby promoting bonding;

[0071] Formation of chemical bonds: Corona treatment induces more active sites on the carboxyl functional groups, promoting the formation of chemical bonds between carboxyl groups and copper, such as the formation of Cu-O or Cu-COOH coordination bonds;

[0072] Changes in functional groups: During the corona treatment process, some carboxyl functional groups will undergo oxidation reactions. The ozone (O3) and oxygen free radicals (O·) generated by corona discharge have strong oxidizing properties. These oxidizing substances can attack the carboxyl (-COOH) functional groups on the surface of the material and oxidize them into other forms of oxygen-containing functional groups, such as keto (-C=O), aldehyde (-CHO) or carbonyl (-CO-). Coordination bonds and covalent bonds can be formed between the oxygen-containing functional groups and copper atoms to obtain coordination compounds and covalent compounds, which transform from simple physical adsorption or weak chemical bonds to stronger chemical bonds, forming a three-dimensional network structure, thereby improving the bonding strength with the copper layer.

[0073] In a further embodiment, corona treatment can enhance the bonding between carboxyl groups and copper atoms. However, the actual bonding strength with copper is affected by the intensity and duration of the corona treatment and the specific properties of the material. Therefore, the parameters of the corona treatment need to be experimentally optimized in subsequent specific implementations according to specific application requirements and material properties.

[0074] (6) Vacuum magnetron sputtering deposition of conductive seed copper layer:

[0075] Magnetron sputtering is a physical vapor deposition (PVD) technology that uses a magnetic field to control the movement of electrons, so that atoms on the target material (copper target) are sputtered out and deposited on the surface of the PPS base film 1 to form a thin film. The magnetron sputtering process may take 1-2 hours, depending on the required thickness of the copper plating layer 2 and the sputtering rate. During the magnetron sputtering process, copper atoms detach from the target material and rearrange on the surface of the base film to form a conductive copper plating layer 2;

[0076] The vacuum magnetron sputtering coating machine used includes a magnetron sputtering gun, a copper target, a vacuum chamber, and a vacuum pump. The magnetron sputtering coating machine can evenly deposit a thin layer of copper on both sides of the base film. This copper layer serves as a conductive seed layer and provides a good attachment point for the subsequent electroplating process.

[0077] (7) Water electroplating thickened conductive copper coating:

[0078] Water electroplating is an electrochemical deposition process. By applying an electric current to the conductive seed layer, copper ions are reduced to copper atoms on the surface of the PPS base film 1 and deposited to form a thickened copper plating layer 2. The water electroplating process may take several hours to more than ten hours. The specific time depends on the required thickness of the copper plating layer 2 and the electroplating rate. During the electroplating process, copper ions obtain electrons on the cathode (base film) and are reduced to copper atoms. This process is an electrochemical reaction. The water electroplating equipment can evenly deposit a thicker copper plating layer 2 on the conductive seed layer, thereby improving the conductivity and mechanical strength of the base film.

[0079] (8) Heating and drying the composite current collector:

[0080] Heating and drying is to evaporate the water and volatile additives on the surface of the composite current collector through the action of heat energy, thereby obtaining a dry copper-plated layer 2. The heating and drying process usually takes 1-2 hours, and the specific time depends on the drying temperature and the characteristics of the material;

[0081] A drying box or tunnel furnace is used in the process, which is equipped with a heating element, a temperature control system and a conveying device. The drying equipment can effectively remove volatile additives on the surface of the composite current collector, such as brighteners, leveling agents, surfactants, etc., thereby reducing the pores in the copper-plated layer 2 and increasing the contact area and mechanical bonding force between the PPS base film 1 and the copper-plated layer 2. Heating causes a certain degree of thermal shrinkage of the PPS base film 1 and the copper-plated layer 2. This shrinkage can increase the mechanical bite between the two, thereby improving the bonding strength. Heating and drying helps to improve the interface contact between the PPS base film 1 and the copper-plated layer 2, because heat energy can help the material surface fit more closely together, thereby obtaining a pure and stable PPS base film 1 and the copper-plated layer 2, which not only improves the quality of the product, but also provides a reliable guarantee for subsequent processing and use;

[0082] During the heating process, heating and drying can promote the chemical reaction between the PPS base film 1 and the copper-plated layer 2. The PPS base film 1 contains carboxyl active functional groups. During the heating process, the carboxyl functional groups on the surface of the copper-plated layer 2 can be oxidized into carbonyl groups (-CO-) and combined with the copper atoms on the surface of the copper-plated layer 2, thereby enhancing the bonding force.

[0083] Specifically, when heated, the copper atoms on the surface of the copper-plated layer 2 can provide empty orbitals, while the oxygen atoms in the carbonyl group of the PPS-based film 1 provide lone pairs of electrons, thereby forming coordination bonds. This coordination effect can form a stable coordination compound, enhance the binding force, and thus improve the bonding strength with the copper layer.

[0084] In a further embodiment, the temperature of heating and drying needs to be properly controlled. Too high a temperature may cause material degradation or oxidation of the copper layer, while too low a temperature may not be sufficient to promote chemical reactions and solvent evaporation. The drying time also needs to be optimized. Too long a time may cause overreaction or material damage, while too short a time may not achieve the desired effect. The atmosphere during the drying process is also very important. Drying in an inert gas or reducing atmosphere can prevent oxidation of the copper layer.

[0085] Heating and drying affects the bonding strength between the PPS base film 1 and the copper-plated layer 2 through physical and chemical mechanisms. According to specific experiments, the drying parameters can be further optimized to achieve high-strength bonding between the PPS base film 1 and the copper-plated layer 2.

[0086] In a further embodiment, the end-capping treatment is optimized to improve the heat resistance of the PPS base film 1; an end-capping agent is added to the carboxylic anhydride (such as terephthalic anhydride) during the polymerization stage of the PPS resin to perform end-capping on the resin, and the end-capping agent chemically reacts with the PPS end group to form a stable end group structure, thereby retaining the heat resistance and mechanical properties while enhancing the bonding force between the PPS base film 1 and the copper plating layer 2. In addition, the polymerization reaction is a nucleophilic substitution reaction between phenol and sodium sulfide in the presence of a catalyst to generate polyphenylene sulfide, and the end-capping process is a chemical reaction between the end-capping agent and the polyphenylene sulfide end group to form a stable end group structure. Through thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) tests, the stability of the high molecular weight PPS resin base film at high temperature is significantly better than that of PP and PET films. Through tensile strength and modulus tests, it is proved that the PPS base film 1 has higher mechanical properties and can withstand a larger traction speed, thereby increasing the production rate.

[0087] In a further embodiment, the magnetron sputtering and evaporation process is optimized, and the parameters of the magnetron sputtering and evaporation equipment are adjusted to adapt to the characteristics of the high molecular weight PPS base film 1. The optimized parameters reduce the number of repeated depositions, reduce the residence time of the PPS base film 1 in the equipment, and reduce the requirements for the sputtering and evaporation equipment during copper plating, while ensuring the uniformity and bonding strength of the copper plating layer 2. After copper plating, surface treatment such as chemical cleaning and plasma treatment is performed, followed by heat treatment such as annealing. The surface treatment removes impurities and oxides and improves the purity and activity of the copper layer. The heat treatment helps the crystallization of the copper layer and the bonding between the PPS base film 1 and the copper plating layer 2. The adhesion test proves that the bonding strength between the optimized PPS base film 1 and the copper plating layer 2 is significantly improved, which is beneficial to the battery recycling performance.

[0088] In a further embodiment, the chemical resistance can be optimized by improving the materials and processes of the PPS base film 1, and a PPS resin with excellent chemical resistance can be selected as the base film material. The performance in the electrolyte can be verified through a chemical stability test. The chemical structure of the PPS resin gives it good stability in the electrolyte, reducing the possibility of dissolution and failure of the composite current collector in the electrolyte. Immersion experiments and electrochemical impedance spectroscopy (EIS) tests have proven that the PPS base film 1 has low solubility and good chemical stability in the electrolyte.

[0089] In summary, by optimizing the preparation of PPS resin, end-capping treatment, surface treatment, the method of obtaining the conductive copper layer and the subsequent heat treatment process, this scheme not only improves the heat resistance and mechanical properties of the PPS base film 1, but also enhances the bonding force between the PPS base film 1 and the copper-plated layer 2, thereby improving the recycling performance of the battery and reducing the risk of dissolution failure of the composite current collector in the electrolyte.

[0090] Performance tests and test results:

[0091] Performance testing:

[0092] PSS film thickness detection

[0093] PSS film thickness uniformity test

[0094] Dielectric constant measurement of PSS film

[0095] PSS film heat resistance test

[0096] Composite current collector thickness test

[0097] Composite current collector surface density test

[0098] Composite current collector oxidation resistance test

[0099] Composite current collector tensile strength test

[0100] Composite current collector adhesion test

[0101] Composite current collector square resistance test

[0102] Composite current collector dyne value test

[0103] Test results:

[0104]

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.

Claims

1. A PPS thin film copper-plated current collector for a battery negative electrode, comprising a base film, characterized in that: The base film is a PPS base film (1) into which carboxyl functional groups are introduced when the molecular chains are terminated, the horizontal surface of the PPS base film (1) is coated with a copper plating layer (2), and a bonding layer (3) is formed on the contact surface between the PPS base film (1) and the copper plating layer (2).

2. The PPS thin film copper-plated current collector for battery negative electrode and the preparation process according to claim 1, characterized in that: The PPS base film (1) is made of polyphenylene sulfide resin, a heat dissipation aid and a microporous particle melt-cast film, and the thickness of the PPS base film (1) is 3 μm.

3. The PPS thin film copper-plated current collector for battery negative electrode and the preparation process according to claim 1, characterized in that: The horizontal surface of the PPS base film (1) is provided with an activation layer by corona, a copper target is deposited on the activation layer by sputtering to form a conductive seed copper layer, the conductive seed copper layer is thickened to form a copper plating layer (2), and the total thickness of the PPS base film (1), the two copper plating layers (2) and the two bonding layers (3) is 6.5 μm.

4. A process for preparing a PPS thin film copper-plated current collector for a battery negative electrode, used for preparing a PPS thin film copper-plated current collector for a battery negative electrode as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1, preparing a high molecular weight polyphenylene sulfide resin, adding a capping agent to cap the polyphenylene sulfide resin, and introducing a carboxyl functional group into the PPS molecular chain; S2, the particles are melted, a heat dissipation aid and microporous particles are added, and the particles are cooled and solidified for granulation; S3, cast film making process; S4, biaxially stretching to form a PPS base film (1); S5. PPS base film (1) surface corona activation treatment to activate and enhance the bonding strength between functional groups and metals; S6, depositing a conductive seed copper layer on the surface of the PPS base film (1) by vacuum magnetron sputtering; S7, thickening the conductive copper plating layer by water electroplating to form a copper plating layer (2); S8, heating, drying and purifying the composite current collector to promote cross-linking and curing between the PPS base film (1) and the copper-plated layer (2) to form a bonding layer (3).

5. The process for preparing a PPS thin film copper-plated current collector for a battery negative electrode according to claim 4, characterized in that: The end-capping agent is carboxylic anhydride, specifically terephthalic anhydride.

6. The process for preparing a PPS thin film copper-plated current collector for a negative electrode of a battery according to claim 4, characterized in that: The heat dissipation aid uses at least one of polybismaleimide resin, silicon nitride fiber, nano-scale silicon dioxide powder, and nano-scale fluorite powder, and the microporous particles use at least one of nano-TiO2, nano-Al2O3, and nano-SiO2.

7. The process for preparing a PPS thin film copper-plated current collector for a negative electrode of a battery according to claim 4, characterized in that: The PPS base film (1) is subjected to double-sided corona treatment using a corona treatment machine, wherein the corona treatment machine comprises a high-voltage power supply, at least two discharge electrodes and a rotating drum.

8. The process for preparing a PPS thin film copper-plated current collector for a negative electrode of a battery according to claim 4, characterized in that: The corona treatment machine can oxidize the carboxyl functional groups at the ends of the PPS molecular chains to produce one or more of keto functional groups, aldehyde functional groups or carbonyl functional groups.

9. The process for preparing a PPS thin film copper-plated current collector for a negative electrode of a battery according to claim 4, characterized in that: The carboxyl functional groups at the ends of the PPS molecular chains are oxidized into carbonyl functional groups by heating, and coordination compounds are formed between the carbonyl functional groups and the copper ions on the surface of the copper plating layer (2).

10. The process for preparing a PPS thin film copper-plated current collector for a negative electrode of a battery according to claim 4, characterized in that: The volatile additives are removed by heating, and the contact surface between the PPS base film (1) and the copper-plated layer (2) undergoes thermal shrinkage due to the heating.